2021
DOI: 10.1136/annrheumdis-2021-220496
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence on ‘Immunogenicity and safety of anti-SARS-Cov-2 mRNA vaccines in patients with chronic inflammatory conditions and immunosuppressive therapy in a monocentric cohort’

Abstract: Patient and public involvement Patients and/or the public were not involved in the design, or conduct, or reporting, or dissemination plans of this research. Patient consent for publication Not required.Ethics approval Ethical approval for this study was obtained according to Italian regulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Anti-CD20 (rituximab) therapy depletes B cells with decreased humoral immune response to recall antigens. Our data are in line with others showing that rituximab affects neutralizing antibodies to COVID-19 vaccination [ 12–14 ]. We proved that in RA patients undergoing treatment with rituximab, even in patients receiving three doses of SARS-CoV-2 vaccinations, the neutralizing antibodies are still significantly lower than in healthy controls.…”
Section: Discussionsupporting
confidence: 93%
“…Anti-CD20 (rituximab) therapy depletes B cells with decreased humoral immune response to recall antigens. Our data are in line with others showing that rituximab affects neutralizing antibodies to COVID-19 vaccination [ 12–14 ]. We proved that in RA patients undergoing treatment with rituximab, even in patients receiving three doses of SARS-CoV-2 vaccinations, the neutralizing antibodies are still significantly lower than in healthy controls.…”
Section: Discussionsupporting
confidence: 93%
“… 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 28 articles were excluded with the following reasons: (1) insufficient data of outcomes, 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 (2) duplicate publications from an overlapping cohort, 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 and (3) case series or cohorts with < 10 patients. 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 A flow diagram of the article selection process is shown in Figure 1 , and the characteristics of each study are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Deepak et al 20 concluded that BCDT has the most prominent effect on antispike protein immunoglobulin G and neutralization titers in the 6 months after dosing, whereas other case series have observed that patients receiving regular rituximab have failed to mount any detectable antibody response, even with a 6-month interval between rituximab dosing and vaccination. 29,30 One of these case series, Salviani et al 29 highlighted 2 cases of patients receiving rituximab for antineutrophil cytoplasmic antibody-associated vasculitis. Although both patients received their last dose of rituximab approximately 7 months prior to vaccination, neither had recovered B-cell counts at time of vaccination and subsequently did not produce a detectable immune response.…”
Section: The Impact Of Biologic Therapy On Response To Covid 19 Vaccines B-celledepleting Therapiesmentioning
confidence: 99%